Socio-economic appraisal of fish sanctuary on livelihood of fishermen in Chikadubi beel of Dingapota Haor, Netrokona, Bangladesh - Alam, Md. Shahin; Rahman, Md. Hashibur; Binti, Nafis Tasneem; Mely, Shayla Sultana; Ahamed, Saokat; Rahman, Md. Moshiur (Archives of Agriculture and Environmental Science, 2023)
The investigation was conducted on the livelihood status of fishers of Chikadubi beel in Dingaputa haor, Netrokona district of Bangladesh for a period of 6 months from August 2020 to December 2020. A total 50 fishers were randomly selected and data were collected from them through direct interview. Focus group discussions were carried out by a previously made checklist. The results showed that the annual income of fishermen varied from BDT 30000 (270.79 USD) to BDT 70000 (631.85 USD). Maximum (58%) fishers were low-income levels from BDT 30000 (270.79 USD) to BDT 40000 (361.05 USD) and trying to shift their professions to other subsidiary professions. Among them 66% of the respondents indicated that this sanctuary is very effective in improving socio-economic status of the fishers. Relatively middle age group (31 to 40 years) dominated in all study areas. Muslim fishermen are the most dominant in the study area. 68% of the fishers live with nuclear families. The highest percentage (62%) fishers can sign only due to economic crisis and lack of awareness about education, (24%) having Primary level education, (14%) have no education as the children dropped out from school before completing their primary education. Housing and sanitation conditions of the fishermen were not well developed. Based on various livelihood parameters, fishermen are leading very poor state of lives. Sanctuary establishment and Community based aquatic resource management strategies may be undertaken with a view to enhance fish production to improve the livelihood condition of the fishers dwelling in the Chikadubi beel area of Dingaputa haor in Bangladesh.